Y-chromosome haplogroup architecture confers susceptibility to azoospermia factor c microrearrangements: a retrospective study - Kuzmanovska, Maja (Croat Med J, 2019)
AIM: To assess the association between azoospermia factor c microrearrangements and semen quality, and between Y-chromosome background with distinct azoospermia factor c microrearrangements and semen quality impairment. METHODS: This retrospective study, carried out in the Research Center for Genetic Engineering and Biotechnology “Georgi D. Efremov,” involved 486 men from different ethnic backgrounds referred for couple infertility from 2002-2017: 338 were azoospermic/oligozoospermic and 148 were normozoospermic. The azoospermia factor c microrearrangements were analyzed with sequence tagged site and sequence family variant markers, quantitative fluorescent polymerase chain reaction, and multiplex ligation probe amplification analysis. The Y-haplogroups of all participants were determined with direct single nucleotide polymorphism typing and indirect prediction with short tandem repeat markers. RESULTS: Our participants had two types of microdeletions: gr/gr and b2/b3; three microduplications: b2/b4, gr/gr, and b2/b3; and one complex rearrangement gr/gr deletion + b2/b4 duplication. Impaired semen quality was not associated with microrearrangements, but b2/b4 and gr/gr duplications were significantly associated with haplogroup R1a (P < 0.001 and P = 0.003, respectively) and b2/b3 deletions with haplogroup E (P = 0.005). There were significantly more b2/b4 duplication carriers in Albanians than in Macedonians with haplogroup R1a (P = 0.031). CONCLUSION: Even though azoospermia factor c partial deletions/duplications and Y-haplogroups were not associated with impaired semen quality, specific deletions/duplications were significantly associated with distinct haplogroups, implying that the Y chromosome background may confer susceptibility to azoospermia factor c microrearrangements.